Liver X receptor agonist T0901317 inhibits the migration and invasion of non-small-cell lung cancer cells in vivo and in vitro. Issue 5 (June 2019) - Lou, Rui; Cao, Haixia; Dong, Shuchen; Shi, Chen; Xu, Xiaoyue; Ma, Rong; Wu, Jianzhong; Feng, Jifeng
Abstract : Liver X receptors are recognized as important regulators of cholesterol, fatty acid metabolism, inflammatory responses, and glucose homeostasis. The antineoplastic properties of synthetic liver X receptor (LXR) agonists (T0901317 and GW3965) have been reported in human carcinomas. Epidermal growth factor tyrosine kinase inhibitor (EGFR-TKI) is a first-line treatment for non-small-cell lung cancer patients with EGFR mutations. We used scratch and transwell assays to analyze cell migration and invasion. We evaluated tumor migration and invasion in vitro using a fluorescent orthotopic lung cancer model. An MMP9 (mouse) enzyme-linked immunosorbent assay kit was used to measure serum MMP9 concentrations. Protein expression was identified by western blot assays. In this study, we determined the effects of T0901317 and/or an EGFR-TKI on the lung cancer cell lines A549 and HCC827-8-1 in vitro and in vivo . We confirmed that the combination of the LXR agonist T0901317 and gefitinib can inhibit the migration and invasion of lung cancer both in vivo and in vitro, and this effect was possibly achieved by the inhibition of the ERK/MAPK signaling pathway. Our study showed that the combination of the LXR agonist T0901317 and gefitinib can inhibit the migration and invasion of lung cancer both in vivo and in vitro .